Olanzapine enhances the effect of conventional drugs in chemotherapy induced nausea and vomiting: A randomized clinical trial - Atefe Khani; Ali Eishy Oskuyi; Rahim Asghari; Hamid Reza Khalkhali; Hamdollah Sharifi (Babol University of Medical Sciences, 2022)
Background: Chemotherapy inducing nausea and vomiting (CINV) is one of the significant   side  effects of anti-cancer treatment, and its full prevention is a potential challenge. This study was done to specify the effect of olanzapine in this setting. Methods: In this randomized, double-blind, clinical trial study, olanzapine was compared with a placebo in combination with dexamethasone and granisetrone in patients with cancer. Patients in the intervention group received dexamethasone , granisetron and olanzapine. Patients in the control group received a placebo instead of olanzapine. Overall, acute nausea and vomiting prevention were the primary and secondary end points; complete response (no nausea,no vomiting) in the delayed period of chemotherapy was the third end point. Response to treatment was evaluated by the Functional Living Index Emesis (FLIE) questionnaire completion in the first, the third and the fifth of chemotherapy. Results:  Percentage reduction in mean±SD nausea and vomiting in the overall phase (0-120 hours) of intervention group compared to the control group respectively were 29.94±2.06, 69.75±2.32 [(57.93% reduction (p<0.001)]. For the acute phase (0-24 hours) were 26.08±2.36, 51.85±2.24 [(47.21% reduction  (p<0.001)], for the delayed phase (24-120 hours), were 31.26±2.57, 67.91±2.12 ,[(55.11% reduction;(p<0.001)] respectively. Conclusion: Olanzapine, along with dexamethasone and granisetron, significantly reduced vomiting and nausea in patients undergoing chemotherapy. No adverse event of olanzapine was observed in the patients.